Status and Challenges of Public Health Emergency Management in China Related to COVID-19 - Cao, Yulong; Shan, Jiao; Gong, Zhizhong; Kuang, Jiqiu; Gao, Yan (Frontiers in Public Health, 2020)
Objective: This study aimed at exploring the current development status and problems of health emergency management in China and provides a reference for improving, constructing, and implementing a public health emergency management system. Methods: Cases of major and severe public health emergencies in China were analyzed along with the relevant health emergency management literature from the last decade. Results: China's health emergency system gradually improved during the study period. Monitoring and early warning systems were significantly strengthened. Material reserves and transfer management systems were constantly improved. However, the operational efficiency of command and decision systems was low, versatile talent accounted for a relatively small proportion, and emergency fund investment was insufficient. Conclusion: Constructing a sound and scientific emergency management mechanism is a lengthy and challenging process. To establish an emergency management mode for public health emergencies that is appropriate for China, it is necessary to solve existing problems and learn from the models and experiences of developed foreign countries.